State capability and challenges to Russia's food security in the twenty-first century - Wegren, Stephen K., 1956- (Studies in contemporary Russia., 2026)
This book offers a rigorous examination of Russia's state capability through the critical lens of food security, revealing profound implications for domestic stability and international relations. Drawing on extensive research, the author demonstrates how food insecurity has historically catalyzed political instability in Russia, explaining the Putin regime's substantial investment in agricultural self-sufficiency since 2014. The analysis extends beyond domestic considerations to interrogate Russia's unique position as the sole major authoritarian grain exporter in a changing global order. It contains compelling evidence that Russia's management of food security challenges constitutes a pivotal factor in contemporary geopolitics. As climate change threatens future Russian grain production, it shows the consequences extend to dependent regimes and global market stability. This timely contribution advances scholarly understanding of how control over fundamental resources influences state capability and international relations. It will be essential reading for researchers and students in Russian studies, international relations, food security, and political economy, as well as policymakers engaged with global food systems and security governance.